2005
DOI: 10.1002/adma.200400860
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Functionalization of Mesoporous Materials: Directly Dispersing Metal Oxides into As‐Prepared SBA‐15 Occluded with Template

Abstract: The unique surface and pore structure of ordered mesoporous materials make them promising for applications in adsorption and catalysis. However, siliceous mesoporous materials usually suffer from a lack of active sites necessary for adsorption or catalysis, and thus their functionalization becomes paramount for application in industry. This is achieved by incorporating guest species such as metals or metal oxides by direct synthesis (one-pot method) or post-modification after synthesis. In the latter process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(61 citation statements)
references
References 15 publications
4
57
0
Order By: Relevance
“…[4] Transmission electron microscopy (TEM) analysis was performed on a FEI Tecnai G 2 20 S-TWIN electron microscope at 200 kV. SEM images were obtained with HITACHI S4800 microscopes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Transmission electron microscopy (TEM) analysis was performed on a FEI Tecnai G 2 20 S-TWIN electron microscope at 200 kV. SEM images were obtained with HITACHI S4800 microscopes.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] But little attention has been paid to the morphological control of mesoporous materials both at the microscale and macroscale levels [5] though specific morphologies are required, for example, for drug delivery, as well as photonic, electronic, and magnetic devices. [6] However, certain requirements of society demand new functional materials with specific morphologies, thus challenging the design and synthesis of mesoporous molecular sieves.…”
Section: Introductionmentioning
confidence: 99%
“…are not incorporated into the framework of SBA-15, but exist in the form of CaWO 4 :Eu 3? nanocrystalline phase in the channels of SBA-15 as that of observed in CuO/SBA-15 composites [39]. Figure 2 displays the WAXRD patterns of SBA-15 and the composites.…”
Section: Resultsmentioning
confidence: 85%
“…Many researchers treated it as a carrier to load metal or oxide to use in the field of catalyst, and also for loading drugs [9,10]. Relevant experiments in our lab had suggested that SBA-15 was used to load the enzyme that can effectively protect the activity of the enzyme, and enhance its reuse.…”
Section: Introductionmentioning
confidence: 98%